The illness reframing process in an ethnic-majority population of older people with incurable cancer: variations of cultural- and existential meaning-making adjustments - Haug, Sigrid Helene Kjørven (Mental health, religion & culture, 2016)
Increasing numbers of older people in Western countries are living with incurable cancer as a chronic disease, receiving palliative care from specialised healthcare contexts. The study's aim was to understand variations of cultural- and existential meaning-making adjustments in a Norwegian majority population of older people with incurable cancer. Semi-structured interviews from 21 participants, aged 70-88, were analysed according to three identified types of belief frames: atheistic/humanistic, religious, and spiritual. Kleinman's medical anthropology cultural framework was adapted and applied deductively together with a reframing metaphor concept in a four-part analytic process. Independent of the differences among the types of belief frames and heterogeneous illness reframing processes, changes in the existential cultural dimension seemed to facilitate psychosocial adjustments in relation to illness, daily living, relationships, and surroundings. The results point to the need for collecting and assessing the function of this type of patient information for better understanding the patient's framework of interpretation, and for identifying treatment-planning resources.